![image](https://tex.z-dn.net/?f=+%5Csqrt%7B37-36%5Ex%7D-5%3D6%5Ex%5C%5C%5Csqrt%7B37-36%5Ex%7D%3D5%2B6%5Ex%5C%5C%28%5Csqrt%7B37-36%5Ex%7D%29%3D%285%2B6%5Ex%29%5E2%5C%5C37-36%5Ex%3D25%2B10%2A6%5Ex%2B36%5Ex%5C%5C2%2A36%5Ex%2B10%2A6%5Ex-12%3D0%5C%5C+2%2A6%5E%7B2x%7D%2B10%2A6%5Ex-12%3D0%7C%3A2%5C%5C6%5E%7B2x%7D%2B5%2A6%5Ex-6%3D0%7Ct%3D6%5Ex%5C%5Ct%5E2%2B5t-6%3D0%5C%5Ct_1%3D-6%5C%5Ct_2%3D1%5C%5C%5C%5C6%5Ex+%5Cneq+-6%5C%5C6%5Ex%3E0%5C%5C%5C%5C6%5Ex%3D1%5C%5C6%5Ex%3D6%5E0%5C%5Cx%3D0%5C%5C%5C%5Cx%3D0)
0\\\\6^x=1\\6^x=6^0\\x=0\\\\x=0" alt=" \sqrt{37-36^x}-5=6^x\\\sqrt{37-36^x}=5+6^x\\(\sqrt{37-36^x})=(5+6^x)^2\\37-36^x=25+10*6^x+36^x\\2*36^x+10*6^x-12=0\\ 2*6^{2x}+10*6^x-12=0|:2\\6^{2x}+5*6^x-6=0|t=6^x\\t^2+5t-6=0\\t_1=-6\\t_2=1\\\\6^x \neq -6\\6^x>0\\\\6^x=1\\6^x=6^0\\x=0\\\\x=0" align="absmiddle" class="latex-formula">